(untitled) (American Journal of Society and Law, 2023)
The Lupin conference was held in 1930 to reach a peace treaty between Iraq and Saudi Arabia. This study aims to highlight the issues and concerns that compelled the Saudi authorities to demand the extradition of Farhan bin Mashhour from Iraq. This study is based on the review and consolidation of secondary data regarding the rebellion of the leaders that was discussed at the Lupin conference in 1930. The sources mentioned in the country library were reviewed, particularly those records were focused that mentioned the rebellious attitudes of foreign politicians to affect the sovereignty and stability of the Kingdom of Saudi Arabia. The study found that the peace treaty in 1930 at the Lupin conference was a win-win situation for Iraq and Saudi Arabia, as it paved the way for future beneficial associations. British officials also agreed to the extradition of Ikhwan leaders from Iraq and handing over to Ibn-Saud.